MODELS OF VARIOGRAM ANALYSIS FOR Pinus brutia TEN. IN ZAWITA FOREST - Muzahim Saeed; Ammar Jasim (Mesopotamia Journal of Agriculture)
Pine is one of the prevalent trees in Zawita forest and a grows naturally on the mountain slopes, to study the competition and spatial analysis in a forest of Zawita, (13) samples were taken from areas of dimensions (60 X 60) m, to each samples measurements of trees and geographical coordinates of each tree and all trees were taken with in each sample. Variogram analysis show that the range of variogram out put for the basal area for all samples did not show any relation between basal area of trees and their locations, as well as, with crown area and with the interaction between them, except for some samples when were excluded the suppressed and medium trees from the variation between the variables. After that, the analysis of Variogram showed a significant correlation the stand variables. The coefficient of determination between the location and basal area, crown area, and their interaction were 0.619, 0.652, and 0.671 respectively.